Peran Pendidikan Agama Islam (PAI) dalam Meningkatkan dan Membangun Toleransi Antar Beragama di Sekolah - Andryadi, Andryadi; Nurdin, Syafruddin; Imamuddin, M.; Zalnur, Muhammad; Balqis, Annisa; Desmawella, Desmawella (IAINU Kebumen, 2026)
This study aims to explore the role of Islamic Religious Education (IRE) in fostering and strengthening attitudes of tolerance among students of different religious backgrounds within the school environment. The method used is a literature study. The research findings reveal that Islamic Religious Education plays a significant role in shaping tolerant attitudes in schools. IRE teachers act as role models as well as educators who convey the values of tolerance to students.The implementation of tolerance values within the school reflects the diversity of the surrounding community and highlights the importance of education in instilling mutual respect among followers of different religions. Therefore, this study recommends that the Islamic Religious Education curriculum be further strengthened to cultivate a young generation that values tolerance and lives in harmony.In addition, support from parents and the wider community is essential in creating inclusive religious education that prioritizes tolerance values. Thus, the results of this study are expected to contribute to the development of more meaningful religious education with a positive impact on the social life of the community.